2004
DOI: 10.1080/00207450490450055
|View full text |Cite
|
Sign up to set email alerts
|

Time Course and Regional Distribution of Cortical Changes During Acute Alcohol Ingestion

Abstract: Behavioral effects of alcohol are known to be greater when the blood alcohol is rising, known as the Mellanby effect, however, research investigating the cortical changes during this period is scarce. The objective of this study was to investigate the effects of consumption of alcohol on cortical activity measured by the electroencephalogram (EEG) during the absorption or rising phase of alcohol. EEG signals were recorded using the entire 10/20 montage system. The experimental design consisted of a repeated me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
2
6
0
1
Order By: Relevance
“…Our EEG results revealed a relative power increase between alcohol and placebo conditions in the theta band (see Fig. ), as already documented in early EEG investigations [Ehlers et al, ; Sanz‐Martin et al, ; Schwarz et al, ; Tran et al, ]. More recent studies have related this specific EEG signature to an increased sensation of euphoria induced by alcohol.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our EEG results revealed a relative power increase between alcohol and placebo conditions in the theta band (see Fig. ), as already documented in early EEG investigations [Ehlers et al, ; Sanz‐Martin et al, ; Schwarz et al, ; Tran et al, ]. More recent studies have related this specific EEG signature to an increased sensation of euphoria induced by alcohol.…”
Section: Discussionsupporting
confidence: 89%
“…More recent studies have related this specific EEG signature to an increased sensation of euphoria induced by alcohol. Specifically, Tran and colleagues interpreted this finding as a result of low cortical arousal during the ascending phase of alcohol intoxication [Tran et al, ], whereas Schwartz and coworkers suggested that the theta power increase is instead due to a de‐inhibition [Schwarz et al, ]. A further issue left unresolved by EEG studies concerns the neuronal generators of this specific theta‐band activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Lukas et al (1986) administered two doses of alcohol (0.347 and 0.695 g/kg) to young men and observed that during the absorption phase, alcohol intoxication resulted in increases in a activity that were positively related to euphoric sensations in the drinkers, whereas during the second phase, both doses of alcohol produced an increase in y activity. Similar results have been reported in other studies with similar alcohol doses (Tran et al, 2004). For example, Sanz-Martin et al…”
Section: Introductionsupporting
confidence: 85%
“…The acute administration of ethanol consistently increases theta and alpha power (particularly within the lower-1 alpha frequency range, 8–10 Hz; e.g. Ilan and Gevins 2001; Lukas et al 1986; Stenberg et al 1994; Tran et al 2004), although alpha power returned to normal levels 60 min after ethanol administration (Lukas et al 1986). Increased alpha power after alcohol consumption has been shown to correlate positively with feelings of euphoria (Lukas et al 1986).…”
Section: Introductionmentioning
confidence: 99%